Reduction of the oxidative damage to H2O2-induced HepG2 cells via the Nrf2 signalling pathway by plant flavonoids Quercetin and Hyperoside - Meijing Zhang; Gaoshuai Zhang; Xiangxing Meng; Xinxin Wang; Jiao Xie; Shaoshu Wang; Biao Wang; Jilite Wang; Suwen Liu; Qun Huang; Xu Yang; Jing Li; et al. (Food Science and Human Wellness)
Hyperoside and quercetin are similar in molecular structures. In this study, the antioxidant regulatory targets of hyperoside and quercetin are mainly in the nuclear factor (erythroid-2-derived)-related factor 2 (Nrf2) pathway predicted by network pharmacology. And the antioxidant effect and mechanism of hyperoside and quercetin were measured and compared in H2O2-induced HepG2 cells and Caenorhabditis elegans. The findings indicated that quercetin was more effective than hyperoside in reducing oxidative damage, which was proved by improved cell viability, decreased reactive oxygen species (ROS) production, decreased cellular apoptosis, and alleviated mitochondrial damage. In addition, quercetin was more efficient than hyperoside in enhancing the expression of Nrf2-associated mRNAs, increasing the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), and reducing the cellular malondialdehyde (MDA) content. Quercetin was superior to hyperoside in prolonging the lifespan of worms, decreasing the accumulation of lipofuscin, inhibiting ROS production, and increasing the proportion of skn-1 in the nucleus. With the Nrf2 inhibitor ML385, we verified that quercetin and hyperoside primarily protected the cells against oxidative damage via the Nrf2 signalling pathway. Furthermore, molecular docking and dynamics simulations demonstrated that the quercetin- Kelch-like ECH-associated protein 1 (Keap1) complex was more stable than the hyperoside-Keap1 complex. The stable structure of the complex might hinder the binding of Nrf2 and Keap1 to release Nrf2 and facilitate its entry into the nucleus to play an antioxidant role. Overall, quercetin had a better antioxidant than hyperoside.